2021
DOI: 10.3390/foods10061226
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Alternative Proteins: Technological, Environmental and Regulatory Aspects of Cultured Meat, Plant-Based Meat, Insect Protein and Single-Cell Protein

Abstract: Food security and environmental issues have become global crises that need transformative solutions. As livestock production is becoming less sustainable, alternative sources of proteins are urgently required. These include cultured meat, plant-based meat, insect protein and single-cell protein. Here, we describe the food safety aspects of these novel protein sources, in terms of their technological backgrounds, environmental impacts and the necessary regulatory framework for future mass-scale production. Brie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
127
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 158 publications
(127 citation statements)
references
References 193 publications
0
127
0
Order By: Relevance
“…Moreover, sources of building proteins for meat analogues other than plants should not be overlooked. Over the years, the possibility of using proteins from fungal fermentation (mycoproteins), insects, microalgae and even non-pathogenic bacterial strains, among others, has been investigated [ 9 ].…”
Section: The Essence Of Meat Analoguesmentioning
confidence: 99%
See 4 more Smart Citations
“…Moreover, sources of building proteins for meat analogues other than plants should not be overlooked. Over the years, the possibility of using proteins from fungal fermentation (mycoproteins), insects, microalgae and even non-pathogenic bacterial strains, among others, has been investigated [ 9 ].…”
Section: The Essence Of Meat Analoguesmentioning
confidence: 99%
“…Stem cells are collected and then differentiated into desired tissues under strictly controlled conditions and in the presence of an appropriate medium. Animal serum-based medium is most commonly used to produce cultured meat, but research is underway to develop serum-free medium for safety and ethical reasons [ 2 , 9 ]. Recent research in meat analogues along with their formulations are shown in Table 1 .…”
Section: The Essence Of Meat Analoguesmentioning
confidence: 99%
See 3 more Smart Citations